Onabotulinum toxin A dosage trends over time for adductor spasmodic dysphonia: A 15‐year experience. (26th August 2015) - Tang, Christopher G.; Novakovic, Daniel; Mor, Niv; Blitzer, Andrew
Abstract : Objectives/Hypothesis: Although onabotulinum neurotoxin A (BoNTA) has been used for over three decades for the treatment of adductor spasmodic dysphonia, no study has been performed to look at the trend of BoNTA dosages across time. The goal of this study is to evaluate the dosage trends to determine if the dosage necessary for voice improvement in patients increases over time. Study Design: Charts were reviewed for patients with 15 years or more of experience. Methods: Linear regression analysis was performed to determine correlation coefficients and trends. Results: Fifty‐five patients receiving BoNTA injections by the senior author (a.b .) for over 15 years were evaluated. Thirty‐nine patients (82% female) met inclusion criteria. Patients received injections over an average of 18.6 years ± 1.36 years, with the longest follow‐up of 21.5 years. Of 39 patients, 16 (41%) had a negative correlation coefficient (Pearson's r) suggesting a decrease over time, whereas 23 (59%) had a positive correlation coefficient suggesting an increase over time. The mean correlation coefficient was 0.139 ± 0.534 and P  < 0.05 in 19 patients and P  > 0.05 in 20 patients. R 2 for all patients were less than 0.75. Conclusions: Onabotulinum neurotoxin A injection dosage trends vary depending on the individual over time. Overall, the dose range appears to be stable in the majority of patients, suggesting that tolerance does not play a significant part in dose variation over time. Level of Evidence: 4. Laryngoscope, 126:678–681, 2016